Peran Praktek GCG Memediasi Pengaruh Struktur Kepemilikan terhadap Kinerja Perusahaan - Siahaan, Fadjar OP (Jurnal Aplikasi Manajemen, 2013)
The purpose of this research is to investigate the effect of ownership structure on firm performanceand GCG, the effect of on firm performance, and GCG as the mediating variable between ownership structure and firm performance. Ownership structure was proxy by public ownership. Firm performance was proxy by ROA and ROS. The sample was selected by using purposive sampling which included 43 observations from 20 companies listed in CGPI rating and listed in Indonesian Stock Exchange during 2009-2011. By using Partial Least Square (PLS), the result of this research shows that (1) public ownership directly reduces performance as measured by using ROA and ROS as well as GCG; (2) GCG implementation doesn't improve ROA; yet, it increases ROS; (3) GCG is not able to mediate ownership structure toward firm performance as perceived from ROS measure